The Effect of Tax Planning on Earnings Management - Posma Sariguna Johnson Kennedy; Theresia Feolina Franstitus; Emerald G.M. Tobing (Asia Pacific Fraud Journal, 2023)
This study aims“to determine the effect of tax planning accompanied by other variables, namely leverage and firm size, on earnings management. The research method is a descriptive and quantitative study using statistical techniques of multiple linear regression analysis. The population are “non-manufacturing companies in the infrastructure sector listed on the Indo-nesia Stock Exchange (IDX) during 2014-2018. Sample selection using the purposive sam-pling technique was obtained from 19 firms. The sources of data in this research are second-ary data. The results show that tax planning and company size affect earnings management. Vice versa, the variable leverage and interest rates don’t affect earnings management. Simul-taneously, leverage, tax planning, and company size significantly influence earnings manage-ment. What needs to be considered, taxpayers undertake a practice to reduce or minimize the tax burden to be paid to the state, often slipping into fraud such as tax evasion